Bubbles and Self-Enforcing Debt - Hellwig, Christian; Lorenzoni, Guido (Econometrica, 2009)
We characterize equilibria with endogenous debt constraints for a general equilibrium econ-omy with limited commitment in which the only consequence of default is losing the ability to borrow in future periods. First, we show that equilibrium debt limits must satisfy a simple con-dition that allows agents to exactly roll over existing debt period by period. Second, we provide an equivalence result, whereby the resulting set of equilibrium allocations with self-enforcing private debt is equivalent to the allocations that are sustained with unbacked public debt or rational bubbles. In contrast to the classic result by Bulow and Rogo § (AER, 1989), positive levels of debt are sustainable in our environment because the interest rate is su¢ciently low to provide repayment incentives. We thank for useful comments the editor, Harald Uhlig, three anonymous referees, Marios Angeletos, Andy